Parents’ attitudes toward the practice of personal naming : a mixed method comparative study between urban and rural societies in Northern Jordan - Abdelrazzaq Tahat, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study outlines the results of an explanatory sequential mixed method survey which is carried out to identify differences in parents’ attitudes toward the selection of their children personal names. The study investigates parents’ attitudes in terms of the factors influencing their choice of a name according to Senif’s (2006) and Bramwell’s (2012) works. The study sample consists of 384 respondents stratified according to two-age groups and place of residence as rural and urban areas in the northern Jordanian Irbid province. A questionnaire and semi-structured interview are used for data collection. Data obtained from the questionnaire are firstly analysed to get initial view and to help constructing the second qualitative instrument in line with the study design. Findings show that young parents of the first age-group are varied in term of religious impact on naming and the inclination to a more fashionable personal names. Urban parents express a favour to media figures on the expense of religious personal names, while rural counterpart emphasises their attachment to personal names stemmed from religious background against the names of public media figures. However, elder parents of the second age-group show different factors influencing their choice which are mainly concentrated on popular names of their surrounding area, the existence of a story that tells about the name’s given, and the impact of peoples’ cultural background. At this group, urban parents demonstrate more positive and constant attitudes to these factors than that expressed by their rural parents. It is quite obvious that young urban parents are shifting to recent names’ trends which are totally opposite to rural parents who still connected to theological beliefs in naming practice. For the elder parents the domain of variation has taken a profound focus on cultural issues which is normally corresponding to interest at this age-stage.